Compound stress in a Norwegian variety of Esperanto. Issue 2 (18th September 2015) - Abrahamsen, Jardar Eggesbø
Abstract : In Norway, there are between 10 and 15 bilingual or multilingual native speakers of Norwegian and Esperanto. This paper discusses some prosodic traits in the Esperanto spoken by one of them. The focus will be on compound stress. The speaker assigns primary stress to the penultimate syllable of words as in Standard Esperanto, including most compounds. Some of the Esperanto compounds, however, display first element primary stress, as in the Norwegian adstrate. In the current dataset, this is especially so for underived nouns. It is proposed that the Norwegian-like pattern is found in compound nouns that are formed spontaneously, while the Standard Esperanto pattern is found in lexicalised compounds, understood as prosodically simplex. For derived compounds in word classes other than nouns, the overall stress pattern is more like that of Standard Esperanto.